1968
DOI: 10.1099/00221287-53-3-321
|View full text |Cite
|
Sign up to set email alerts
|

The Mating-type Systems of the Myxomycetes Physarum rigidum and P. flavicomum

Abstract: SUMMARYThree geographical collections (isolates) of myxomycetes originally identified as PhysarumJlavicomum were found to be heterothallic and the clones established from each isolate were divided into two mating types. Previous studies of six isolates of P.Javicomum showed that they could be divided into three groups. Mating occurred within groups but not between groups, and within each group there were two or more mating types. When the new isolates were crossed to the original isolates, they conformed to tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1968
1968
1979
1979

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The present work was done with the PHILIPPINE 11 isolate while they worked with the AFRICA isolate. These two isolates formed a compatible allelic series (Henney & Henney, 1968).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work was done with the PHILIPPINE 11 isolate while they worked with the AFRICA isolate. These two isolates formed a compatible allelic series (Henney & Henney, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Axenic clones (myxamoebae) of the organisms studied were established by the methods previously described (Henney & Henney, 1968). Axenic plasmodia were produced by mixing two compatible clones together on half-strength corn meal agar…”
Section: Methodsmentioning
confidence: 99%
“…YA question mark after a number indicates that spores from interstrain crosses are non-viable. " Henney (1967). ""Henney (l968)-includes Pliysarum bilgramii.…”
Section: Results-mentioning
confidence: 99%
“…Both homoth~llic a?d hete.rothallic isolates have been found in Fuligo septtca, Physarum cinereum, Physarum pusillum, Didymium diiiorme, Didymium iridis, and Didymium~i gripes (see Table 2 for references). Interstenle mating groups have been reported for Physarun: [lavicomum (Henney, 1967), Physarum globuli- ferum , Physarum polycephalum (Collins, 1975a), Physarum pusillum (Collins, Alexopoulos and Henney, 1964), and Physarum rigidum (Henney, 1967;Henney and Henney, 1968). Studies on the DNA content and chromosome numbers have revealed a remarkable amount of variation both between and within strains of the two species which have been well examined: Physarum polycephalum (Ross, 1961(Ross, , 1966Guttes, Guttes and Rusch, 1961;von Stosch, Van Zul-Pischinger and Dersch, 1964;Koevenig and Jackson, 1966;Mohberg andRusch, 1971, Mohberg et al, 1973) and Didymium iridis (Therrien, 1966;Yemma and Therrien, 1972;Therrien and Yemma, 1974).…”
Section: Results-mentioning
confidence: 99%
“…Most notable have been those investigations with Physarum polycephalum (Dee, 1962(Dee, , 1966, Didymium iridis (Collins, 1961(Collins, , 1963(Collins, , 1965Ling, 1964, 1968;Mukherjee and Zabka, 1964), Physarum pusillum (Collins, 1962), Physarumfiavicomum (Henney, 1967;Henney and Henney, 1968) and Physarum rigidum (Henney and Henney, 1968).…”
Section: Introductionmentioning
confidence: 99%